Phenotypic Variability of Local Latvian Common Bean (Phaseolus vulgaris L.) and Its Position Within European Germplasm - Gunārs Lācis; Shreya Jagtap; Laila Dubova; Tetiana Harbovska; Daniels Udalovs; Liene Ziediņa; Ina Alsiņa (International Journal of Plant Biology)
Common beans (Phaseolus vulgaris L.) are considered a socially and economically important crop, with the biggest growers in India, Myanmar, and Brazil. Traditionally, common beans are also grown in most parts of Europe, including Latvia, where cultivation areas have remained relatively constant since the middle of the last century. This is explained by the plant’s higher thermal requirements compared to peas and faba beans more widely grown here. Despite this, landraces adapted to local conditions have been developed, whose origin and potential relationship with another European common bean germplasm is very limited. Therefore, the study aimed to characterise the morphology of the common bean germplasm collected and grown in Latvia to identify the most valuable material for further crop development and evaluate the local landraces in the European common bean germplasm context. The 28 genotypes representing Latvian landraces and European reference genotypes were phenotyped using 26 traits of bean seeds, pods, leaves, flowers, and stems, which were evaluated according to an internationally applied methodology. Latvian varieties showed phenotypical variability and characteristics that were different from those found in other European regions, showing the significance of the germplasm under study and highlighting the need for conservation. Local varieties (landraces) are reservoirs of unique genetic traits. Their adaptability to local environmental conditions, resistance to pests and diseases, and their potential to enhance nutritional quality make them invaluable resources for in situ conservation efforts and targeted genetic improvement programmes. Emphasising the utilisation of these landraces can contribute to sustainable agriculture, climate resilience, and food security.